2014
DOI: 10.1007/s12253-014-9825-3
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Effects of Quercitrin on DLD-1 Colon Cancer Cell Line

Abstract: Quercetin, which is the most abundant bioflavonoid compound, is mainly present in the glycoside form of quercitrin. Although different studies indicated that quercitrin is a potent antioxidant, the action of this compound is not well understood. In this study, we investigated whether quercitrin has apoptotic and antiproliferative effects in DLD-1 colon cancer cell lines. Time and dose dependent antiproliferative and apoptotic effects of quercitrin were subsequently determined by WST-1 cell proliferation assay,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Thus, optimizing an efficient A. rhizogenes-mediated hairy root culture system could be a promising approach to supply flavonoids (quercetin) from radish biomass. Quercetin has gained a lot of attention as powerful antioxidant and antifibrotic compound with cytoprotective effects (Cincin et al 2014). In medical science, it has been demonstrated that quercetin, in a dose of 150 mg day −1 , downregulates from the systolic pressure (Egert et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, optimizing an efficient A. rhizogenes-mediated hairy root culture system could be a promising approach to supply flavonoids (quercetin) from radish biomass. Quercetin has gained a lot of attention as powerful antioxidant and antifibrotic compound with cytoprotective effects (Cincin et al 2014). In medical science, it has been demonstrated that quercetin, in a dose of 150 mg day −1 , downregulates from the systolic pressure (Egert et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The literature reports that compound 1 (diglycosylated flavonoid) showed antiallergic actions (Ichikawa, Ogura, Lijima, 1986), high antioxidant potential (Nascimento et al, 2013) and antileishmanial activities (Muzitano et al, 2006a). Moreover, quercetrin (2) protected skin from UVB-induced inflammation (Yin et al, 2013), displayed antioxidant (Aderogba, Okoh, Idowu, 2005;Tai et al, 2014) and antileishmanial activities (Muzitano et al, 2006b), showed antiproliferative and apoptotic effects in colon cancer cells (Cincin et al, 2015), demonstrated gastroprotective actions (Mota et al, 2009) and showed intestinal anti-inflammatory effects (Camuesco et al, 2004). Júnior et al, (2014) reported that quercitrin was present in Croton campestris extracts at 2.34% and might be involved in gastroprotective activities against ethanol, acidified ethanol-, and indomethacin-induced gastric lesions.…”
mentioning
confidence: 99%
“…Also flavonoids present in fruit extracts as catechin, epicatechin, and rutin were able to inhibit MDA-MB 231 and HCT116 proliferation at concentrations higher than 100 μM (Hayes et al, 2006 ; Li et al, 2009 ). Quercitrin has antiproliferative and apoptotic effect on colon cancer cells (Cincin et al, 2015 ). Given the cytotoxic properties reported in literature for xanthones (Bennet and Lee, 1989 ; Vieira and Kijjoa, 2005 ; Demirkiran, 2007 ), 1,2,3,5-tetrahydroxyxanthone may also contribute to the final effect observed on tumor cells.…”
Section: Resultsmentioning
confidence: 99%